Conspiracy Beliefs About Birth Control: Barriers to Pregnancy Prevention Among African Americans of Reproductive Age - Thorburn, Sheryl; Bogart, Laura M. (Health education & behavior, 2005)
This article examines the endorsement of conspiracy beliefs about birth control (e.g., the belief that birth control is a form of Black genocide) and their association with contraceptive attitudes and behavior among African Americans. The authors conducted a telephone survey with a random sample of 500 African Americans (aged 15-44). Many respondents endorsed birth control conspiracy beliefs, including conspiracy beliefs about Black genocide and the safety of contraceptive methods. Stronger conspiracy beliefs predicted more negative attitudes toward contraceptives. In addition, men with stronger contraceptive safety conspiracy beliefs were less likely to be currently using any birth control. Among current birth control users, women with stronger contraceptive safety conspiracy beliefs were less likely to be using contraceptive methods that must be obtained from a health care provider. Results suggest that conspiracy beliefs are a barrier to pregnancy prevention. Findings point to the need for addressing conspiracy beliefs in public health practice.